POLYMORPHISM OF OSTEOPROTEGERIN GENE IN INDONESIAN MEN WITH PERIODONTITIS - EI, AUERKARI; I., SAVITRI; SLC, MASULILI; A. W., SUHARTONO (International Journal of Applied Pharmaceutics, 2019)
Objective: This work aimed to clarify the association of the severity of periodontitis and polymorphism in osteoprotegerin (OPG) (T950C) in Indonesian men. Methods: For DNA extraction, blood serum samples were used from 100 consenting Indonesian males for whom also the status of periodontitis had been classified as mild, moderate, or severe. Polymerase chain reaction and restriction fragment length polymorphism techniques were applied to evaluate OPG (T950C) polymorphism, using Hind II restriction enzyme and electrophoresis on agarose gel to separate the indicative fragments. Results: The genotype distribution of the OPG (T950C) polymorphism had an appearance of an increasing percentage of TT genotype (allele T) with increasing severitPeriodontitisy of periodontitis. The CC genotype was relatively rare (1%) in the tested Indonesian male population. Conclusions: The results show no significant association between the severity of periodontitis and polymorphism of OPG (T950C) in Indonesian men.